The Effectiveness of Peer Group WhatsApp on Adolescent Knowledge and Attitudes about Risky Sexual Behavior - Arisani, Greiny; Wahyuni, Seri (Universitas Airlangga, 2023)
Background: Nowadays problems of teenagers are very complex and worrying, both those that arise from within themselves and from outside themselves. Various internal and external factors that affect adolescents will also have an impact on adolescents to have negative and unhealthy attitudes and behaviors (high-risk behaviors). Efforts to increase knowledge and attitudes in adolescents can be used in preventing risky sexual behavior through WhatsApp peer groups. Objective: This study analyzes the effectiveness of the WhatsApp peer group on the knowledge and attitudes of adolescents about risky sexual behavior in Isen Mulang Senior High School, Palangka Raya City. Methods: This study is a quasi-experimental study with two groups, pretest-posttest with a control group design which was carried out from July to September 2020. The population in this study were all adolescents who were in the age range of 15-21 years in Isen mulang Senior High School at SMA Isen Mulang, Palangka Raya city numbered 169 people with the sampling technique in this study using consecutive sampling with a sample of 31 respondents in the intervention group and 31 respondents in the control group. Results: There is a significant difference in the average value of knowledge (P-value = 0.000) and attitude score (P-value = 0.000) before and after the intervention in each group, there is a significant difference in increasing knowledge (P-value = 0.045) and attitude (P-value = 0.048) between the intervention group and the control group. The average increase in knowledge scores and attitude scores of the intervention group was higher than the control group. Conclusion: WhatsApp peer groups are considered effective in increasing adolescent knowledge and attitudes about risky sexual behavior. WhatsApp peer groups can be used as dynamic communication media and become one of the alternative choices in providing health education to adolescents other than face-to-face.